Binder composition for heat-resistant layer of non-aqueous secondary battery, slurry composition for heat-resistant layer of non-aqueous secondary battery, heat-resistant layer for non-aqueous secondary battery, and non-aqueous secondary battery

The use of a particulate polymer with specific cyano and hydroxyl group-containing monomer units in the binder composition for non-aqueous secondary battery heat-resistant layers addresses the issue of insufficient peel strength and adhesion, resulting in improved performance of secondary batteries.

JP7619267B2Active Publication Date: 2025-01-22ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021542863
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-08-21
Publication Date
2025-01-22
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

Conventional slurry compositions for non-aqueous secondary battery heat-resistant layers lack sufficient peel strength and adhesion to the base material, necessitating improvements to enhance the performance of secondary batteries.

Method used

A binder composition for non-aqueous secondary battery heat-resistant layers containing a particulate polymer with specific molar fractions of cyano and hydroxyl group-containing monomer units, and a predetermined parameter M OH /S value, is used to form a slurry composition that achieves high peel strength and improved adhesion.

Benefits of technology

The proposed binder composition enables the formation of a heat-resistant layer with significantly enhanced peel strength and adhesion, leading to improved cycle characteristics and heat shrinkage resistance in non-aqueous secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619267000001
    Figure 0007619267000001
Patent Text Reader

Abstract

This binder composition for a heat-resistant layer of a non-aqueous secondary battery contains a particulate polymer including a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, wherein a value (MOH / S), which is obtained by dividing the value MOH of the mole fraction of the hydroxyl group-containing monomer unit in the particulate polymer by the value S (µm2) of the surface area of the particulate polymer, is 0.40 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder composition for a heat-resistant layer of a non-aqueous secondary battery, a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, a heat-resistant layer for a non-aqueous secondary battery, and a non-aqueous secondary battery. [Background technology]

[0002] Non-aqueous secondary batteries such as lithium ion secondary batteries (hereinafter sometimes simply referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Secondary batteries generally include battery components such as electrodes (positive and negative electrodes) and a separator that separates the positive and negative electrodes. Conventionally, battery components that include a protective layer for improving heat resistance, i.e., a heat-resistant layer, have been used as such battery components.

[0003] Here, the heat-resistant layer of the secondary battery may be formed by binding non-conductive particles with a binder. Such a heat-resistant layer is usually formed by preparing a slurry composition in which non-conductive particles and a binder are dissolved or dispersed in a dispersion medium such as water (hereinafter, referred to as a "slurry composition for non-aqueous secondary battery heat-resistant layer" and may be abbreviated as a "slurry composition for heat-resistant layer"). This slurry composition for heat-resistant layer is applied to a substrate such as a separator substrate or an electrode substrate, and then dried.

[0004] In recent years, in order to achieve further improvements in the performance of secondary batteries, attempts have been made to improve the binder composition used in forming the heat-resistant layer (see, for example, Patent Document 1). Patent Document 1 discloses a slurry for a lithium ion secondary battery porous membrane, which includes non-conductive particles, a water-soluble polymer having an acidic group-containing monomer unit, and a particulate polymer, the amount of the water-soluble polymer relative to the amount of the non-conductive particles being within a predetermined range, and the BET specific surface area of ​​the non-conductive particles being within a predetermined range. More specifically, Patent Document 1 discloses a slurry for a porous membrane, which includes a particulate polymer obtained by polymerizing a particulate polymer obtained by using a monomer composition containing acrylonitrile as a nitrile group-containing monomer, butyl acrylate as a (meth)acrylic acid ester monomer, methacrylic acid as an ethylenically unsaturated acid monomer, and allyl glycidyl ether and N-methylolacrylamide as crosslinkable monomers under predetermined conditions, a water-soluble polymer, and non-conductive particles. The slurry for a porous membrane described in Patent Document 1 can form a porous membrane that can exhibit heat resistance, that is, a heat-resistant layer. And, according to the slurry for a porous membrane described in Patent Document 1, the high-temperature cycle characteristics of the obtained lithium ion secondary battery can be excellent. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 148577 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in recent years, there has been a demand for further improvement in the performance of secondary batteries, and the conventional slurry composition has room for improvement in terms of increasing the adhesion between the heat-resistant layer formed using the slurry composition and the substrate (e.g., separator substrate or electrode substrate) on which the heat-resistant layer is formed. More specifically, there has been a demand for a slurry composition that can increase the peel strength of the obtained heat-resistant layer and increase the adhesion between the heat-resistant layer and the substrate.

[0007] Therefore, an object of the present invention is to provide a binder composition for a non-aqueous secondary battery heat-resistant layer that can prepare a slurry composition for a non-aqueous secondary battery heat-resistant layer that can form a non-aqueous secondary battery heat-resistant layer having sufficiently high peel strength. Another object of the present invention is to provide a slurry composition for a heat-resistant layer for a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery having sufficiently high peel strength. An object of the present invention is to provide a heat-resistant layer for a non-aqueous secondary battery having a sufficiently high peel strength, and a non-aqueous secondary battery including the heat-resistant layer. [Means for solving the problem]

[0008] The present inventors have conducted intensive research in order to solve the above problems. The present inventors have found that a heat-resistant layer having a sufficiently high peel strength can be formed when a particulate polymer containing a hydroxyl group-containing monomer unit and a cyano group-containing monomer unit is used, and the value (parameter) obtained by dividing the molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer by the surface area of ​​the particulate polymer satisfies a predetermined condition, and have completed the present invention.

[0009] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the binder composition for a heat-resistant layer of a non-aqueous secondary battery of the present invention is a binder composition for a heat-resistant layer of a non-aqueous secondary battery containing a particulate polymer, the particulate polymer containing a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, and further, a molar fraction value M of the hydroxyl group-containing monomer unit in the particulate polymer. OH The surface area value S (μm 2 ) divided by (M OH In this way, the hydroxyl group-containing monomer unit and the cyano group-containing monomer unit are included, and the value (M OH According to a binder composition containing a particulate polymer in which the ratio of the binder resin to the binder resin is 0.40 or more, a slurry composition capable of forming a heat-resistant layer having a sufficiently high peel strength can be prepared. In addition, when a polymer "contains a monomer unit," it means that "a polymer obtained by using that monomer contains a repeating unit derived from the monomer." In addition, the "molar fraction" of a certain monomer unit (each repeating unit) contained in a polymer is the ratio of the number of moles of a certain monomer unit contained in a polymer when the total number of moles of all repeating units (all monomer units) contained in the polymer is taken as 1. Furthermore, "mole fraction" means 1 H-NMR and 13 It can be measured using nuclear magnetic resonance (NMR) techniques such as C-NMR.

[0010] Here, in the binder composition for a heat-resistant layer of a non-aqueous secondary battery of the present invention, the particulate polymer preferably has a volume average particle size of 0.30 μm or less and a molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer of 0.02 or more. When the volume average particle size of the particulate polymer is 0.30 μm or less and the molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer is 0.02 or more, the heat shrink resistance of the obtained heat-resistant layer can be improved, and further, the cycle characteristics of the obtained secondary battery can be improved. The "volume average particle size" of the particulate polymer means the particle size (D50) at which the cumulative volume calculated from the small diameter side in the particle size distribution (volume basis) measured by a laser diffraction method becomes 50%.

[0011] In addition, in the binder composition for a heat-resistant layer of a non-aqueous secondary battery of the present invention, the molar fraction of the cyano group-containing monomer unit in the particulate polymer is preferably 0.07 or less. If the molar fraction of the cyano group-containing monomer unit in the particulate polymer is 0.07 or less, the heat shrinkage resistance of the obtained heat-resistant layer can be further improved.

[0012] Furthermore, in the binder composition for a heat-resistant layer of a non-aqueous secondary battery of the present invention, the swelling degree of the particulate polymer in an electrolyte solution is preferably 8.0 times or less. If the swelling degree of the particulate polymer in an electrolyte solution is 8.0 times or less, the cycle characteristics of the obtained secondary battery can be improved. The degree of swelling is the degree of swelling with respect to an electrolytic solution (a solution obtained by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate and ethyl methyl carbonate at a mass ratio of 3:7), and can be measured by the method described in the examples.

[0013] The present invention also aims to advantageously solve the above problems, and the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention is characterized in that it contains non-conductive particles and any of the binder compositions for a non-aqueous secondary battery heat-resistant layer described above. In this way, a heat-resistant layer having a sufficiently high peel strength can be formed by using a slurry composition containing non-conductive particles and any of the binder compositions described above.

[0014] In the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention, the non-conductive particles preferably have a volume average particle diameter of 0.7 μm or less. If the non-conductive particles have a volume average particle diameter of 0.7 μm or less, the heat shrink resistance of the obtained heat-resistant layer can be improved. The volume average particle diameter of the non-conductive particles means the particle diameter (D50) at which the cumulative volume calculated from the small diameter side in the particle size distribution (volume basis) measured by a laser diffraction method becomes 50%.

[0015] The present invention aims to advantageously solve the above problems, and the heat-resistant layer for a non-aqueous secondary battery of the present invention is characterized in that it is formed using the above-mentioned slurry composition for a heat-resistant layer for a non-aqueous secondary battery. In this way, the heat-resistant layer formed from the above-mentioned slurry composition has a sufficiently high peel strength.

[0016] The present invention also aims to advantageously solve the above problems, and the nonaqueous secondary battery of the present invention is characterized by comprising the above-mentioned heat-resistant layer for nonaqueous secondary batteries. Thus, a secondary battery comprising a battery member having the above-mentioned heat-resistant layer has excellent battery characteristics. Effect of the Invention

[0017] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery heat-resistant layer, which can prepare a slurry composition for a non-aqueous secondary battery heat-resistant layer capable of forming a non-aqueous secondary battery heat-resistant layer having sufficiently high peel strength. Moreover, according to the present invention, it is possible to provide a slurry composition for a heat-resistant layer for a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery having a sufficiently high peel strength. According to the present invention, it is possible to provide a heat-resistant layer for a nonaqueous secondary battery having a sufficiently high peel strength, and a nonaqueous secondary battery including the heat-resistant layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described in detail. Here, the binder composition for non-aqueous secondary battery heat-resistant layer of the present invention can be used to prepare the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention. And, the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention can be used to form a heat-resistant layer of a non-aqueous secondary battery such as a lithium ion secondary battery. Furthermore, the heat-resistant layer for non-aqueous secondary battery of the present invention is characterized in that it is formed from the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention. Also, the non-aqueous secondary battery of the present invention is characterized in that it comprises a heat-resistant layer for non-aqueous secondary battery prepared using the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention.

[0019] (Binder composition for heat-resistant layer of non-aqueous secondary battery) The binder composition of the present invention contains a particulate polymer, and may optionally further contain a dispersion medium and other components. Here, the binder composition of the present invention is characterized in that the above-mentioned particulate polymer contains a hydroxyl group-containing monomer unit and a cyano group-containing monomer unit, and further, the molar fraction value M of the hydroxyl group-containing monomer unit in the particulate polymer is OH is the surface area value S (μm 2 ) divided by (M OH / S) is 0.40 or more.

[0020] Since the binder composition of the present invention contains a particulate polymer that satisfies the above-mentioned specified properties, the obtained heat-resistant layer can be adhered to the substrate with sufficient strength, and as a result, the peel strength of the heat-resistant layer can be sufficiently increased. Although the reason why the above-mentioned effect is obtained by using the binder composition containing the above-mentioned specified particulate polymer is not clear, it is believed that the value of the molar fraction M of the hydroxyl group-containing monomer unit is more than 100%. OH is the surface area value S (μm 2 ) divided by (M OH This is presumably because a particulate polymer containing hydroxyl group-containing monomer units at such a frequency that the ratio (R / S) is 0.40 or more can be strongly adhered to an object to be adhered.

[0021] <Particulate polymer> The particulate polymer contained in the binder composition of the present invention is a component that can function as a binder in the heat-resistant layer formed using the slurry composition, and is a component that imparts adhesiveness to the heat-resistant layer formed using the slurry composition containing the binder composition, and is a component that can hold the non-conductive particles contained in the heat-resistant layer so that they do not detach from the heat-resistant layer. The particulate polymer is a water-insoluble particle formed by a specific polymer. In the present invention, the particle is "water-insoluble" when 0.5 g of the polymer is dissolved in 100 g of water at 25° C., and the insoluble content is 90% by mass or more.

[0022] Here, the particulate polymer contains a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, and may optionally contain other monomer units. Various monomer units will be described in detail below.

[0023] <<Cyano group-containing monomer unit>> The cyano group-containing monomer unit is a monomer unit obtained by polymerizing a cyano group-containing monomer. Examples of the cyano group-containing monomer that can form the cyano group-containing monomer unit include α,β-unsaturated nitrile monomers such as acrylonitrile and methacrylonitrile. These may be used alone or in combination of two or more in any ratio.

[0024] The molar fraction of the cyano group-containing monomer unit in the particulate polymer is preferably 0.07 or less, more preferably 0.06 or less, and even more preferably 0.05 or less, assuming that the total number of moles of all repeating units contained in the particulate polymer is 1. If the molar fraction of the cyano group-containing monomer unit in the particulate polymer is equal to or less than the upper limit, the heat shrink resistance of the obtained heat-resistant layer can be improved. The molar fraction of the cyano group-containing monomer unit must be greater than 0, and is preferably 0.01 or more. The presence of the cyano group-containing monomer unit when preparing the particulate polymer can increase the stability of the particulate polymer during polymerization.

[0025] <<Hydroxyl group-containing monomer unit>> The hydroxyl group-containing monomer unit is a monomer unit obtained by polymerizing a hydroxyl group-containing monomer. Examples of hydroxyl group-containing monomers that can form the hydroxyl group-containing monomer unit include hydroxyalkyl acrylates such as hydroxymethyl acrylate, hydroxymethyl methacrylate, β-hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate; and N-hydroxyalkyl acrylamides such as N-hydroxymethyl acrylamide (N-methylol acrylamide), N-hydroxymethyl methacrylamide (N-methylol methacrylamide), N-hydroxyethyl acrylamide, and N-hydroxyethyl methacrylamide. These may be used alone or in combination of two or more at any ratio. Among these, N-methylolacrylamide, β-hydroxyethyl acrylate, hydroxyethyl methacrylate, and N-hydroxyethyl acrylamide are preferred, and N-methylolacrylamide and β-hydroxyethyl acrylate are more preferred.

[0026] The molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer is preferably 0.02 or more, more preferably 0.03 or more, and preferably 0.10 or less, and more preferably 0.08 or less, where the total number of moles of all repeating units contained in the particulate polymer is 1. If the molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer is the above-mentioned lower limit or more, the adhesion between the obtained heat-resistant layer and the substrate is increased, thereby improving the cycle characteristics of the obtained secondary battery. In addition, if the molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer is the above-mentioned upper limit or less, the polymerization stability during preparation of the particulate polymer can be improved.

[0027] <<Other monomer units>> The other monomer units are not particularly limited, and include (meth)acrylic acid ester monomer units, acidic group-containing monomer units, ethylenically unsaturated carboxylic acid amide monomer units, crosslinkable monomer units, aromatic vinyl monomer units, fluorine atom-containing monomer units, and aliphatic conjugated diene monomer units. In this specification, (meth)acrylic means acrylic or methacrylic.

[0028] [(Meth)acrylic acid ester monomer unit] The (meth)acrylic acid ester monomer unit is a monomer unit obtained by polymerizing a (meth)acrylic acid ester monomer. Examples of alkyl (meth)acrylic acid ester monomers that can form the (meth)acrylic acid ester monomer unit include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate (n-butyl acrylate), isobutyl acrylate, t-butyl acrylate, n-amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate (2-ethylhexyl acrylate), 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, hexyl acrylate, nonyl acrylate, ... Examples of the acrylate include acrylates such as lauryl acrylate, stearyl acrylate, and benzyl acrylate; and methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, isodecyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, and benzyl methacrylate. These may be used alone or in combination of two or more at any ratio. Among them, as the (meth)acrylic acid ester monomer, n-butyl acrylate (n-butyl acrylate) and 2-ethylhexyl acrylate (2-ethylhexyl acrylate) are preferred.

[0029] When the particulate polymer contains a (meth)acrylic acid ester monomer unit, the molar fraction of the (meth)acrylic acid ester monomer unit in the particulate polymer is preferably more than 0.5, more preferably 0.6 or more, and more preferably less than 0.98, more preferably 0.95 or less, and even more preferably 0.93 or less, where the total number of moles of all repeating units contained in the particulate polymer is 1. If the molar fraction of the (meth)acrylic acid ester monomer unit in the particulate polymer is within the above range, the peel strength of the obtained heat-resistant layer can be further increased. In this specification, a particulate polymer having a molar fraction of the (meth)acrylic acid ester monomer unit of more than 0.5 is referred to as a (meth)acrylic acid ester copolymer.

[0030] [Acidic group-containing monomer unit] The acidic group-containing monomer unit is a monomer unit obtained by polymerizing an acidic group-containing monomer. Examples of the acidic group include acidic functional groups such as -COOH group (carboxylic acid group); -SO3H group (sulfonic acid group); and phosphoric acid groups such as -PO3H2 group and -PO(OH)(OR) group (R represents a hydrocarbon group). Therefore, examples of the acidic group-containing monomer that can form the acidic group-containing monomer unit include monomers having these acidic groups. In addition, examples of the acidic group-containing monomer include monomers that can generate the above-mentioned acidic groups by hydrolysis. Specific examples of such acidic group-containing monomers include acid anhydrides that can generate carboxylic acid groups by hydrolysis. The various acidic group-containing monomers listed below may be used alone or in combination of two or more at any ratio.

[0031] Examples of monomers having a carboxylic acid group include monocarboxylic acids, dicarboxylic acids, anhydrides of dicarboxylic acids, and derivatives thereof. Examples of monocarboxylic acids include acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, isocrotonic acid, and the like. Examples of dicarboxylic acids include carboxylic acid group-containing monomers such as maleic acid, fumaric acid, itaconic acid, and methylmaleic acid. Examples of acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride, and the like.

[0032] Examples of the monomer having a sulfonic acid group include sulfonic acid group-containing monomers such as vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and 2-(N-acryloyl)amino-2-methyl-1,3-propane-disulfonic acid.

[0033] Examples of monomers having a phosphate group such as -PO3H2 group and -PO(OH)(OR) group (R represents a hydrocarbon group) include phosphate group-containing monomers such as 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In this specification, (meth)acryloyl means acryloyl or methacryloyl.

[0034] In addition, the salts of the above-mentioned various monomers can also be used as the acidic group-containing monomer. Among the above-mentioned acidic group-containing monomers, it is preferable to use a carboxylic acid group-containing monomer, and it is further preferable to use the above-mentioned monocarboxylic acid, and it is particularly preferable to use methacrylic acid.

[0035] When the particulate polymer contains an acidic group-containing monomer unit, the molar fraction of the acidic group-containing monomer unit in the particulate polymer is preferably 0.01 or more and 0.1 or less, where the total molar number of all repeating units contained in the particulate polymer is 1. When the molar fraction of the acidic group-containing monomer unit in the particulate polymer is within the above range, the heat shrink resistance of the obtained heat-resistant layer can be further improved.

[0036] [Ethylenically unsaturated carboxylic acid amide monomer unit] The ethylenically unsaturated carboxylic acid amide monomer unit is a monomer unit obtained by polymerizing an ethylenically unsaturated carboxylic acid amide monomer. Examples of the ethylenically unsaturated carboxylic acid amide monomer include acrylamide, methacrylamide, N-methoxymethylacrylamide, and N-methoxymethylmethacrylamide. These may be used alone or in combination of two or more at any ratio. Among them, acrylamide and methacrylamide are preferred, and acrylamide is more preferred.

[0037] When the particulate polymer contains an ethylenically unsaturated carboxylic acid amide monomer unit, the molar fraction of the ethylenically unsaturated carboxylic acid amide monomer unit in the particulate polymer is preferably 0.01 or more, more preferably 0.02 or more, and preferably 0.1 or less, more preferably 0.08 or less, assuming that the total molar number of all repeating units contained in the particulate polymer is 1. If the molar fraction of the ethylenically unsaturated carboxylic acid amide monomer unit in the particulate polymer is within the above range, the peel strength of the obtained heat-resistant layer can be further increased.

[0038] [Cross-linking monomer unit] The crosslinkable monomer unit is a structural unit having a structure formed by polymerizing a crosslinkable monomer. The crosslinkable monomer is a monomer that can form a crosslinked structure during or after polymerization, triggered by heating or energy ray irradiation. More specifically, the crosslinkable monomer unit includes a crosslinkable monomer having a thermally crosslinkable crosslinkable group and one olefinic double bond per molecule (hereinafter, sometimes referred to as "crosslinkable monomer 1"); a crosslinkable monomer having two or more olefinic double bonds per molecule (hereinafter, sometimes referred to as "crosslinkable monomer 2"); and the like. These may be used alone or in combination of two or more types at any ratio. The crosslinkable monomer unit does not include those corresponding to the various monomer units described above and below.

[0039] Examples of the thermally crosslinkable crosslinking group that can be contained in the crosslinkable monomer 1 include an epoxy group, an oxetanyl group, an oxazoline group, and a combination thereof. Specific examples of the crosslinkable monomer 1 having an epoxy group as a thermally crosslinkable crosslinking group include glycidyl acrylate and glycidyl methacrylate.

[0040] Further, examples of the crosslinkable monomer 2 include allyl (meth)acrylate, allyl (meth)acrylate ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate. In this specification, (meth)acrylate means acrylate or methacrylate. Among them, allyl (meth)acrylate is preferred, and allyl methacrylate is more preferred.

[0041] When the particulate polymer contains a crosslinkable monomer unit, the molar fraction of the crosslinkable monomer unit in the particulate polymer is preferably 0.001 or more and 0.1 or less, with the total molar number of all repeating units contained in the particulate polymer being 1. If the molar fraction of the crosslinkable monomer unit in the particulate polymer is within the above range, the cycle characteristics of the obtained secondary battery can be improved.

[0042] [Aromatic vinyl monomer unit] The aromatic vinyl monomer unit is a monomer unit obtained by polymerizing an aromatic vinyl monomer. The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene, α-methylstyrene, vinyltoluene, and divinylbenzene. These aromatic vinyl monomers may be used alone or in combination of two or more at any ratio. Among them, styrene is preferred as the aromatic vinyl monomer.

[0043] When the particulate polymer contains an aromatic vinyl monomer unit, the molar fraction of the aromatic vinyl monomer unit in the particulate polymer is preferably 0.1 to 0.3, where the total molar number of all repeating units contained in the particulate polymer is 1. When the molar fraction of the aromatic vinyl monomer unit in the particulate polymer is within the above range, the heat shrink resistance of the obtained heat-resistant layer can be improved.

[0044] [Fluorine atom-containing monomer unit] The fluorine atom-containing monomer unit is a monomer unit obtained by polymerizing a fluorine atom-containing monomer. Examples of the fluorine atom-containing monomer include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, vinyl chloride trifluoride, vinyl fluoride, and perfluoroalkyl vinyl ether. These may be used alone or in combination of two or more at any ratio.

[0045] [Aliphatic conjugated diene monomer unit] The aliphatic conjugated diene monomer unit is a monomer unit obtained by polymerizing an aliphatic conjugated diene monomer. Examples of the aliphatic conjugated diene monomer include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, and 2-chloro-1,3-butadiene. These may be used alone or in combination of two or more kinds in any ratio.

[0046] <<Properties>> [Parameter MOH / S] The particulate polymer is a polymer having a molar fraction M of hydroxyl group-containing monomer units in the particulate polymer. OH is the surface area value S (μm 2 ) divided by (M OH / S) is required to be 0.40 or more. OH When the value of / S is 0.40 or more, the peel strength of the obtained heat-resistant layer can be sufficiently increased. Furthermore, from the viewpoint of further improving the balance between the peel strength, heat shrinkage resistance, and cycle characteristics of the obtained heat-resistant layer, the parameter M OH It is more preferable that the value of / S is 0.45 or more.

[0047] [Volume average particle size] The volume average particle diameter of the particulate polymer is preferably 0.08 μm or more, more preferably 0.10 μm or more, preferably 0.30 μm or less, more preferably 0.25 μm or less, even more preferably 0.20 μm or less, and particularly preferably 0.18 μm or less. If the volume average particle diameter of the particulate polymer is the above lower limit or more, the air permeability of the obtained heat-resistant layer can be suppressed from being excessively decreased, and the rate characteristics of the obtained secondary battery can be improved. If the volume average particle diameter of the particulate polymer is the above upper limit or less, the heat shrink resistance of the obtained heat-resistant layer can be improved. The volume average particle size of the particulate polymer can be adjusted, for example, by changing the type and amount of the monomer, polymerization initiator and / or polymerization accelerator used in the preparation of the particulate polymer.

[0048] [Swelling degree in electrolyte] The swelling degree of the particulate polymer in the electrolyte is preferably 8.0 times or less, more preferably 4.5 times or less, further preferably 4.2 times or less, and particularly preferably 4.0 times or less. The swelling degree of the particulate polymer in the electrolyte is usually more than 1.0 times, and preferably 1.5 times or more. If the swelling degree of the particulate polymer is equal to or less than the upper limit, the cycle characteristics of the obtained secondary battery can be improved. If the swelling degree of the particulate polymer meets the lower limit, the rate characteristics of the obtained secondary battery can be improved.

[0049] <<Method for preparing particulate polymer>> Here, the polymerization method of the particulate polymer is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. may be used. In addition, as the polymerization reaction, addition polymerization such as ionic polymerization, radical polymerization, living radical polymerization, etc. may be used. In addition, the polymerization solvent, emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. that can be used in the polymerization can be general ones, and the amount of each of them can be the amount generally used.

[0050] In addition, the content of the particulate polymer in the binder composition of the present invention is not particularly limited.

[0051] <Dispersion medium> Examples of the dispersion medium that may be optionally contained in the binder composition of the present invention include water, organic solvents (e.g., esters, ketones, alcohols), and mixtures thereof. The binder composition of the present invention may contain one type of organic solvent, or may contain two or more types of organic solvents. Among them, water is preferred as the dispersion medium.

[0052] <Other ingredients> The binder composition of the present invention may contain a water-soluble polymer, a reinforcing material, a leveling agent, a wetting agent, a dispersant, a viscosity modifier, an electrolyte additive, a preservative, an antifungal agent, an antifoaming agent, a polymerization inhibitor, and a binder other than the particulate polymer as described above. These are not particularly limited as long as they do not affect the battery reaction, and known ones can be used. In addition, the other components may be used alone or in combination of two or more kinds in any ratio.

[0053] The water-soluble polymer that the binder composition for a non-aqueous secondary battery heat-resistant layer may optionally contain is a component that can function as a viscosity adjuster in the binder composition and in a slurry composition containing such a binder composition. The term "water-soluble" for a polymer means that when 0.5 g of the polymer is dissolved in 100 g of water at 25°C, the insoluble matter is less than 1.0 mass %.

[0054] The water-soluble polymer is not particularly limited, and various thickening polysaccharides can be used. As the thickening polysaccharide, carboxymethylcellulose, methylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, polyvinyl alcohol, polyacrylic acid or a salt thereof is preferably used, and carboxymethylcellulose or a salt thereof is particularly preferably used. Examples of carboxymethylcellulose salts include sodium salts, ammonium salts, etc. The thickening polysaccharides may be used alone or in combination of two or more kinds at any ratio.

[0055] In addition, the wetting agent that may be optionally contained in the binder composition for a non-aqueous secondary battery heat-resistant layer is not particularly limited, and may be an ethylene oxide / propylene oxide-based surfactant (EO·PO-based surfactant), a fluorine-based surfactant, a silicon-based surfactant, etc. Among them, it is preferable to use an EO·PO-based surfactant or a fluorine-based surfactant, and it is more preferable to use an EO·PO-based surfactant. The dispersant is not particularly limited, and examples of the dispersant that can be used include polycarboxylic acids such as polyacrylic acid, sodium polycarboxylates such as sodium polyacrylate, ammonium polycarboxylates such as ammonium polyacrylate, polycarboxylate sulfonic acid copolymers, sodium polycarboxylate sulfonic acid copolymers, ammonium polycarboxylate sulfonic acid copolymers, etc. Among these, it is preferable to use sodium polyacrylate. Specific examples of the components other than the wetting agent and dispersant described above are not particularly limited, but include those described in WO 2012 / 115096.

[0056] <Preparation of binder composition for non-aqueous secondary battery heat-resistant layer> The binder composition of the present invention can be prepared by mixing the above-mentioned particulate polymer with any other components as necessary by a known method. Specifically, the binder composition can be prepared by mixing the above-mentioned components using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a Filmix. For example, when the particulate polymer is prepared by polymerizing it in an aqueous solution, the state of the aqueous dispersion of the particulate polymer can be used as the binder composition as it is.

[0057] (Slurry composition for non-aqueous secondary battery heat-resistant layer) The slurry composition of the present invention is a composition used for forming a heat-resistant layer, and contains non-conductive inorganic particles and the above-mentioned binder composition, and optionally contains other components. That is, the slurry composition of the present invention usually contains non-conductive particles, a particulate polymer, and a dispersion medium, and optionally contains other components. And, since the slurry composition of the present invention contains the above-mentioned binder composition, it can form a heat-resistant layer with sufficiently high peel strength.

[0058] <Non-conductive particles> Here, the non-conductive particles contained in the slurry composition for the heat-resistant layer are not particularly limited, and include particles made of inorganic materials (i.e., non-conductive inorganic particles) and particles made of organic materials (i.e., non-conductive organic particles) that are stable in the use environment of the secondary battery and electrochemically stable. Among them, non-conductive inorganic particles are preferred. Preferred examples of non-conductive inorganic particles include inorganic oxide particles such as aluminum oxide (alumina, Al2O3), aluminum oxide hydrate (boehmite, AlOOH), gibbsite (Al(OH)3), silicon oxide, magnesium oxide (magnesia), magnesium hydroxide, calcium oxide, titanium oxide (titania), barium titanate (BaTiO3), ZrO, and alumina-silica composite oxide; nitride particles such as aluminum nitride and boron nitride; covalent crystal particles such as silicon and diamond; sparingly soluble ion crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay fine particles such as talc and montmorillonite; and the like. Among these, from the viewpoint of improving the adhesion between the heat-resistant layer and the substrate, the non-conductive particles are preferably particles made of alumina (alumina particles), particles made of boehmite (boehmite particles), particles made of titania (titania particles), and particles made of barium sulfate (barium sulfate particles), more preferably alumina particles, boehmite particles, and barium sulfate particles, and even more preferably alumina particles and barium sulfate particles. In addition, these particles may be subjected to element substitution, surface treatment, solid solution, etc., as necessary. In addition, these particles may be used alone or in combination of two or more kinds.

[0059] The non-conductive organic particles are organic compounds different from the particulate polymers used as binders. That is, the non-conductive organic particles do not have binding properties. Preferred examples of the non-conductive organic particles include various crosslinked polymer particles such as crosslinked polymethylmethacrylate, crosslinked polystyrene, crosslinked polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked products, polystyrene, polyimide, polyamide, polyamideimide, melamine resin, phenolic resin, and benzoguanamine-formaldehyde condensate, and heat-resistant polymer particles such as polysulfone, polyacrylonitrile, polyaramid, polyacetal, and thermoplastic polyimide. In addition, modified products and derivatives of these can also be used as the non-conductive organic particles. These particles may be used alone or in combination of two or more types. The glass transition temperature of the organic particles as the non-conductive particles is preferably higher than 20° C., and is usually not higher than 350° C. The glass transition temperature of the organic particles can be measured in accordance with JIS K7121.

[0060] The volume average particle diameter of the non-conductive particles is preferably 0.7 μm or less, more preferably 0.5 μm or less, and even more preferably 0.4 μm or less. If the volume average particle diameter of the non-conductive particles is equal to or less than the above upper limit, the heat shrink resistance of the obtained heat-resistant layer can be improved. The volume average particle diameter of the non-conductive particles can usually be 0.05 μm or more. The volume average particle diameter of the non-conductive particles can be measured by applying a laser analysis method according to JIS Z 8825 to non-conductive particles pretreated according to JIS Z 8824.

[0061] <Binder composition> As the binder composition, the above-mentioned binder composition of the present invention is used. In addition, the content of the above-mentioned predetermined particulate polymer in the slurry composition is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, in terms of solid content per 100 parts by mass of non-conductive particles, from the viewpoint of suppressing excessive decrease in the air permeability of the obtained heat-resistant layer. In addition, in terms of further increasing the peel strength of the obtained heat-resistant layer, the content of the above-mentioned predetermined particulate polymer in the slurry composition is preferably 1 part by mass or more, more preferably 1.2 parts by mass or more, and even more preferably 1.5 parts by mass or more, in terms of solid content per 100 parts by mass of non-conductive particles. In addition, when the slurry composition contains a water-soluble polymer, which is an optional component described later, the content of the particulate polymer is preferably greater than the content of the water-soluble polymer.

[0062] <Other ingredients> Other components that can be blended in the slurry composition are not particularly limited, and include the same components as those that can be blended in the binder composition of the present invention. The other components may be used alone or in combination of two or more in any ratio. The content of the water-soluble polymer as an optional component in the slurry composition is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, in terms of solid content, per 100 parts by mass of non-conductive particles (particularly non-conductive inorganic particles) from the viewpoint of further improving the heat shrink resistance of the obtained heat-resistant layer. Also, the content of the water-soluble polymer as an optional component in the slurry composition is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, in terms of solid content, per 100 parts by mass of non-conductive particles (particularly non-conductive inorganic particles) from the viewpoint of suppressing an excessive decrease in the air permeability of the obtained heat-resistant layer. In addition, the content of the above-mentioned wetting agent, which is an optional component in the slurry composition, is preferably 0.01 parts by mass or more, preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less per 100 parts by mass of non-conductive particles (particularly non-conductive inorganic particles). If the content of the wetting agent is equal to or more than the above lower limit, the peel strength of the obtained heat-resistant layer can be further increased. In addition, if the content of the wetting agent is equal to or less than the above upper limit, the cycle characteristics of the secondary battery can be improved. Furthermore, the content of the above-mentioned dispersant, which is an optional component in the slurry composition, is preferably 0.1 parts by mass or more, preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less per 100 parts by mass of non-conductive particles (particularly non-conductive inorganic particles). By setting the content of the dispersant to the above lower limit or more, the heat shrink resistance of the heat-resistant layer can be improved. Furthermore, by setting the content of the dispersant to the above upper limit or less, the cycle characteristics of the secondary battery can be improved.

[0063] <Preparation of Slurry Composition for Non-Aqueous Secondary Battery Heat-Resistant Layer> The above-mentioned slurry composition can be prepared by mixing the above-mentioned components by a known mixing method as described above in the section <Preparation of binder composition for non-aqueous secondary battery heat-resistant layer>.

[0064] (Heat-resistant layer for non-aqueous secondary batteries) The heat-resistant layer of the present invention is formed from the above-mentioned slurry composition of the present invention, and can be formed, for example, by applying the above-mentioned slurry composition to the surface of a suitable substrate to form a coating film, and then drying the formed coating film. That is, the heat-resistant layer of the present invention is made of the dried product of the above-mentioned slurry composition, and usually contains at least non-conductive particles and particulate polymers. Note that, since each component contained in the heat-resistant layer is contained in the above-mentioned slurry composition, the preferred ratio of each component is the same as the preferred ratio of each component in the slurry composition. Furthermore, since the heat-resistant layer of the present invention is formed from the slurry composition of the present invention containing the binder composition of the present invention, the peel strength is sufficiently high.

[0065] <Base material> Here, there is no limitation on the substrate to which the slurry composition is applied, and for example, a coating film of the slurry composition may be formed on the surface of a release substrate, the coating film may be dried to form a heat-resistant layer, and the release substrate may be peeled off from the heat-resistant layer. In this way, the heat-resistant layer peeled off from the release substrate may be used as a free-standing film to form a battery component of a secondary battery. However, from the viewpoint of omitting the step of peeling off the heat-resistant layer and increasing the production efficiency of the battery component, it is preferable to use a separator substrate or an electrode substrate as the substrate. Specifically, it is preferable to apply the slurry composition onto the separator substrate or the electrode substrate, and it is more preferable to apply the slurry composition onto the separator substrate.

[0066] <<Separator substrate>> The separator substrate is not particularly limited, but may be any of known separator substrates such as an organic separator substrate. The organic separator substrate is a porous member made of an organic material, and examples of the organic separator substrate include microporous membranes or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc., and polyethylene microporous membranes and nonwoven fabrics are preferred because of their excellent strength.

[0067] <<Electrode base material>> The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, but examples thereof include an electrode substrate in which an electrode mixture layer containing an electrode active material and a binder is formed on a current collector. The current collector, the electrode active materials (positive electrode active material, negative electrode active material) and the binders for the electrode mixture layer (positive electrode mixture layer binder, negative electrode mixture layer binder) in the electrode mixture layer, and the method for forming the electrode mixture layer on the current collector may be any known method, such as those described in JP 2013-145763 A.

[0068] <Method of forming heat-resistant layer> The heat-resistant layer can be formed on a substrate such as the separator substrate or electrode substrate by the following method. 1) A method in which the slurry composition of the present invention is applied to the surface of a substrate (in the case of an electrode substrate, the surface on the electrode mixture layer side; the same applies below) and then dried; 2) a method of immersing a substrate in the slurry composition of the present invention and then drying the substrate; and 3) A method in which the slurry composition of the present invention is applied onto a release substrate, followed by drying to produce a heat-resistant layer, and then the obtained heat-resistant layer is transferred onto the surface of the substrate. Among these, the method 1) is particularly preferred because it is easy to control the thickness of the heat-resistant layer. Specifically, the method 1) includes a step of applying a slurry composition onto a substrate (application step) and a step of drying the slurry composition applied onto the substrate to form a heat-resistant layer (drying step).

[0069] <<Coating process>> In the coating step, the method for coating the slurry composition on the substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.

[0070] <<Drying process>> In the drying step, the method for drying the slurry composition on the substrate is not particularly limited and may be any known method. Examples of the drying method include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with infrared rays or electron beams.

[0071] <Thickness of heat-resistant layer> The thickness of the heat-resistant layer is preferably 4 μm or less, more preferably 3 μm or less, even more preferably 2.5 μm or less, and particularly preferably 2 μm or less. The thickness of the heat-resistant layer is not particularly limited, but may be, for example, 0.2 μm or more. If the thickness of the heat-resistant layer is equal to or less than the upper limit, the cycle characteristics of the obtained secondary battery can be improved. If the thickness of the heat-resistant layer is equal to or more than the lower limit, the heat-resistant layer has excellent heat shrinkage resistance.

[0072] (Non-aqueous secondary battery) The secondary battery of the present invention includes the heat-resistant layer of the present invention described above. More specifically, the secondary battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte, and the heat-resistant layer is included in at least one of the positive electrode, the negative electrode, and the separator, which are battery components.

[0073] <Positive electrode, negative electrode and separator> At least one of the positive electrode, negative electrode, and separator used in the secondary battery of the present invention is a battery member having the heat-resistant layer of the present invention described above. Note that the positive electrode, negative electrode, and separator not having the heat-resistant layer of the present invention are not particularly limited, and known positive electrodes, negative electrodes, and separators can be used.

[0074] <Electrolyte> As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is usually used. As the supporting electrolyte, for example, a lithium salt is used in a lithium ion secondary battery. As the lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. are listed. Among them, LiPF6, LiClO4, and CF3SO3Li are preferred because they are easily dissolved in a solvent and show a high degree of dissociation. Note that one type of electrolyte may be used alone, or two or more types may be used in combination. Usually, the lithium ion conductivity tends to be higher as the supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0075] The organic solvent used in the electrolyte is not particularly limited as long as it can dissolve the supporting electrolyte, but for example, in a lithium ion secondary battery, alkyl carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and the like are preferably used. A mixture of these solvents may also be used. Among them, carbonates are preferred because they have a high dielectric constant and a wide stable potential range. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. Also, known additives such as vinylene carbonate (VC) may be added to the electrolytic solution.

[0076] <Method of manufacturing non-aqueous secondary battery> The non-aqueous secondary battery of the present invention can be manufactured, for example, by stacking a positive electrode and a negative electrode with a separator therebetween, wrapping or folding the stack according to the shape of the battery as necessary, placing the stack in a battery container, injecting an electrolyte into the battery container, and sealing the container. At least one of the positive electrode, negative electrode, and separator is a member with a heat-resistant layer. In order to prevent the occurrence of an internal pressure rise in the secondary battery, overcharging and discharging, etc., a fuse, an overcurrent prevention element such as a PTC element, an expanded metal, a lead plate, etc. may be provided as necessary. The shape of the secondary battery may be, for example, any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc. EXAMPLES

[0077] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified. In addition, in a polymer produced by polymerizing a plurality of types of monomers, the ratio (or molar fraction) of a monomer unit formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio or molar fraction) of the certain monomer in the total monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the measurement and evaluation of various attributes were carried out according to the following methods.

[0078] <Volume average particle size of particulate polymer> The volume average particle diameter of the particulate polymer prepared in the examples and comparative examples was measured by a laser diffraction method. Specifically, an aqueous dispersion (adjusted to a solid content concentration of 0.1% by mass) containing the measurement target (particulate polymer) was used as a sample. Then, in the particle size distribution (volume basis) measured using a laser diffraction type particle size distribution measuring device (manufactured by Beckman Coulter, Inc., product name "LS-13 320"), the particle diameter D50 at which the cumulative volume calculated from the small diameter side is 50% was taken as the volume average particle diameter. <Parameter M OH / S> For the particulate polymers prepared in the Examples and Comparative Examples, the molar fraction M of the hydroxyl group-containing monomer units in the particulate polymers OH is the surface area value S (μm 2 ) divided by (M OH / S) was calculated according to the following formula: M OH / S = (Mole fraction value of hydroxyl group-containing monomer units in the particulate polymer) OH ) ÷ (4π × (volume average particle size of particulate polymer / 2) (μm) 2 ) The molar fraction of the hydroxyl group-containing monomer unit M OH The molar fraction of the hydroxyl group-containing monomer in the monomer composition used in preparing each of the particulate polymers was used as the molar fraction. The molar fractions of the other various monomer units were also calculated using the formula M OH The values ​​were calculated in the same manner as for the values ​​of and are shown in Table 1. As described above, the surface area of ​​the particulate polymer S (μm2 ) was calculated using the volume average particle diameter D50 obtained as described above, assuming that the shape of the particulate polymer was a perfect sphere. <Degree of swelling with electrolyte> The particulate polymer prepared in the Examples and Comparative Examples was molded into a film with a thickness of about 0.1 mm, which was cut into a square of about 2 cm to prepare a test piece, and the mass of the test piece (mass before immersion) was measured. The test piece was then immersed in an electrolyte at a temperature of 60° C. for 72 hours. The immersed test piece was pulled out, the electrolyte was wiped off, and the mass (mass after immersion) was immediately measured, and the value of (mass after immersion) / (mass before immersion) was taken as the swelling degree. The electrolyte used was a solution in which LiPF6 was dissolved at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate and ethyl methyl carbonate at a mass ratio of 3:7. The smaller the swelling degree value obtained, the higher the electrolyte resistance of the particulate polymer. <Water solubility of particulate polymer> 0.5 g of the particulate polymer prepared in each of the Examples and Comparative Examples was dissolved in 100 g of water at a temperature of 25° C. In all of the Examples and Comparative Examples, it was confirmed that the insoluble matter was 90% by mass or more.

[0079] <Adhesion of heat-resistant layer for non-aqueous secondary batteries> The separators with heat-resistant layers prepared in the examples and comparative examples were each cut into a width of 10 mm and a length of 50 mm to prepare test pieces. Next, a stainless steel (SUS) plate with double-sided tape (Nitto Denko Corporation, No. 5608) attached was prepared, and the heat-resistant layer side of the test piece was attached to the double-sided tape. One end of the separator substrate was then pulled at a speed of 50 mm / min so that the peeling surface was at an angle of 180°, and the peel strength was measured and evaluated according to the following criteria. A higher peel strength indicates a higher adhesion between the separator substrate and the heat-resistant layer. A: Peel strength 50N / m or more B: Peel strength 30N / m or more and less than 50N / m C: Peel strength less than 30N / m <Heat shrinkage resistance of heat-resistant layer for non-aqueous secondary batteries> The separators with heat-resistant layers produced in the Examples and Comparative Examples were cut into squares measuring 12 cm wide x 12 cm long, and a square measuring 10 cm on a side was drawn inside the square to prepare a test piece. The test piece was then placed in a thermostatic chamber at 150°C and left for 1 hour, after which the change in area of ​​the square drawn inside (= {(area of ​​square before left - area of ​​square after left) / area of ​​square before left} x 100%) was calculated as the thermal shrinkage rate and evaluated according to the following criteria. The smaller this thermal shrinkage rate, the better the heat shrinkage resistance of the heat-resistant layer. A: Heat shrinkage rate is less than 10% B: Heat shrinkage rate is 10% or more and less than 20% C: Heat shrinkage rate is 20% or more <Cycle characteristics of non-aqueous secondary batteries> The lithium ion secondary batteries prepared in the examples and comparative examples were left to stand for 24 hours in an environment at 25° C. Thereafter, at 25° C., they were charged to 4.2 V (cutoff condition: 0.02 C) by a constant voltage constant current (CC-CV) method at a charge rate of 1 C, and discharged to 3.0 V by a constant current (CC) method at a discharge rate of 1 C, and the initial capacity C0 was measured. Furthermore, the same charge / discharge operation was repeated in a 25°C environment, and the capacity C1 after 300 cycles was measured. The capacity retention rate ΔC = (C1 / C0) × 100 (%) was calculated and evaluated according to the following criteria. The higher the capacity retention rate, the less the decrease in discharge capacity and the better the cycle characteristics. A: Capacity retention rate ΔC is 85% or more B: Capacity retention rate ΔC is 75% or more and less than 85% C: Capacity retention rate ΔC is less than 75%

[0080] Example 1 <Preparation of Aqueous Dispersion Containing Particulate Polymer A> To a reactor equipped with a stirrer, 90 parts of ion-exchanged water, 0.05 parts of sodium dodecylbenzenesulfonate (manufactured by Kao Chemical Corporation, "Neopelex G-15") as an emulsifier, and 0.23 parts of ammonium persulfate were supplied, the gas phase was replaced with nitrogen gas, and the temperature was raised to 70°C. On the other hand, in a separate vessel, 50 parts of ion-exchanged water, 0.1 parts of sodium dodecylbenzenesulfonate as an emulsifier, 2.2 parts of acrylonitrile (AN) as a cyano group-containing monomer, 2.5 parts of N-methylol acrylamide (NMA) as a hydroxyl group-containing monomer, and 92.0 parts of n-butyl acrylate (BA), 2.1 parts of methacrylic acid (MAA), and 1.2 parts of acrylamide (AAm) as other monomers were mixed to obtain a monomer composition. This monomer composition was continuously added to the reactor over 4 hours to carry out polymerization. During the addition, the reaction was carried out at 80°C. After the addition was completed, the reaction was terminated by stirring for another 3 hours at 80°C to produce an aqueous dispersion containing particulate polymer A (binder composition for heat-resistant layer). For the obtained particulate polymer A, the volume average particle diameter, parameter M OH The molecular weight distribution (Mg / S) and the swelling degree in the electrolyte were measured or calculated. The results are shown in Table 1. The obtained particulate polymer A was a (meth)acrylic acid ester copolymer (ACL) having a molar fraction of butyl acrylate units, which are acrylic acid ester monomer units, of 0.87. <Preparation of Slurry Composition for Heat-Resistant Layer> Alumina particles (AKP-30, Sumitomo Chemical Co., Ltd., volume average particle diameter D50 (catalog value): 0.3 μm) were used as the non-conductive particles, sodium polyacrylate (Aron T-50, Toa Gosei Co., Ltd.) was used as the dispersant, and carboxymethylcellulose with an etherification degree of 0.8 to 1.0 (Daicel FineChem Co., Ltd., D1220) was used as the water-soluble polymer. The viscosity of a 1% aqueous solution of the water-soluble polymer was 10 to 20 mPa s. 100 parts of non-conductive particles, 0.5 parts of dispersant, and ion-exchanged water were mixed and processed for 1 hour with a bead mill (LMZ015, manufactured by Ashizawa Finetech Co., Ltd.) to obtain a dispersion. Further, the binder composition for heat-resistant layer prepared as described above was mixed with an amount equivalent to 4 parts of particulate polymer A in terms of solid content, an amount equivalent to 1.5 parts of a 4% aqueous solution of carboxymethylcellulose in terms of solid content, and 0.3 parts of an ethylene oxide / propylene oxide surfactant (Noptex ED-052, manufactured by San Nopco Co., Ltd.) as a wetting agent to prepare a slurry composition for heat-resistant layer with a solid content concentration of 40% by mass. <Preparation of a separator with a heat-resistant layer on one side> A polyethylene separator substrate (manufactured by Asahi Kasei Corporation, ND509, thickness: 9 μm) was prepared. The slurry composition for heat-resistant layer prepared above was applied to the surface of the prepared separator substrate, and dried at a temperature of 50° C. for 3 minutes to obtain a separator with a heat-resistant layer (thickness of heat-resistant layer: 2 μm) having a heat-resistant layer on one side. The obtained separator with a heat-resistant layer was used to evaluate the adhesion and heat shrinkage resistance of the heat-resistant layer according to the above. The results are shown in Table 1. <Preparation of negative electrode> In a 5MPa pressure vessel equipped with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium persulfate as a polymerization initiator were placed, thoroughly stirred, and then heated to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the mixture was cooled to stop the polymerization reaction, and a mixture containing a particulate binder (styrene-butadiene copolymer) was obtained. After adjusting the pH to 8 by adding a 5% aqueous sodium hydroxide solution to the mixture, unreacted monomers were removed by heating and vacuum distillation. The mixture was then cooled to 30°C or less to obtain an aqueous dispersion containing a binder for the negative electrode. Into a planetary mixer, 48.75 parts of artificial graphite (theoretical capacity: 360 mAh / g) as a negative electrode active material, 48.75 parts of natural graphite (theoretical capacity: 360 mAh / g), and 1 part of carboxymethyl cellulose as a thickener in terms of solid content were added. Further, the mixture was diluted with ion-exchanged water so that the solid content concentration was 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the negative electrode binder obtained as described above in terms of solid content were added, and kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity was 3000±500 mPa·s (measured with a B-type viscometer at 25°C and 60 rpm), to prepare a slurry composition for a negative electrode mixture layer. The negative electrode mixture layer slurry composition was applied to the surface of a 15 μm-thick copper foil current collector with a comma coater in an amount of 11±0.5 mg / cm 2Thereafter, the copper foil coated with the slurry composition for the negative electrode composite layer was transported at a speed of 400 mm / min through an oven at a temperature of 80° C. for 2 minutes and then through an oven at a temperature of 110° C. for 2 minutes to dry the slurry composition on the copper foil, thereby obtaining a negative electrode raw sheet in which a negative electrode composite layer was formed on a current collector. Thereafter, the negative electrode composite layer side of the produced negative electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 11 t (tons) to obtain a negative electrode composite layer density of 1.60 g / cm 3 Thereafter, the negative electrode was left for one week in an environment of a temperature of 25±3° C. and a relative humidity of 50±5%. <Preparation of positive electrode> The planetary mixer is equipped with the lithium composite oxide active material NMC111, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A slurry composition for a positive electrode composite layer was prepared by adding 96 parts of ethyl acetate (O2, 96 parts), 2 parts of acetylene black (HS-100, manufactured by Denka Co., Ltd.) as a conductive material, and 2 parts of polyvinylidene fluoride (KF-1100, manufactured by Kureha Chemical Co., Ltd.) as a binder, and further adding and mixing N-methyl-2-pyrrolidone (NMP) as a dispersion medium so that the total solids concentration was 67%. Next, the obtained slurry composition for the positive electrode mixture layer was applied to an aluminum foil having a thickness of 20 μm, which was a current collector, with a comma coater in an amount of 20±0.5 mg / cm. 2 The coating was applied so that the result was as follows. The slurry composition on the aluminum foil was dried by transporting the aluminum foil at a speed of 200 mm / min through an oven at a temperature of 90° C. for 2 minutes and then through an oven at a temperature of 120° C. for 2 minutes, thereby obtaining a positive electrode raw sheet in which a positive electrode composite layer was formed on the current collector. Thereafter, the positive electrode composite layer side of the prepared positive electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 14 tonnes, so that the density of the positive electrode composite layer became 3.40 g / cm 3 Thereafter, the positive electrode was left for one week in an environment of a temperature of 25±3° C. and a relative humidity of 50±5%. <Preparation of secondary battery> A wound cell (equivalent to a discharge capacity of 520 mAh) was prepared using the above negative electrode, positive electrode, and separator, and placed in an aluminum packaging material. Then, a 1.0 M LiPF6 solution (solvent: mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (mass ratio), additive: vinylene carbonate 2 volume % (solvent ratio)) was filled into the aluminum packaging material as an electrolyte. Furthermore, in order to seal the opening of the aluminum packaging material, the aluminum packaging material was closed by heat sealing at a temperature of 150 ° C., and a lithium ion secondary battery was manufactured. The cycle characteristics were evaluated using this lithium ion secondary battery. The results are shown in Table 1.

[0081] (Examples 2 to 7, 9, and 11) In synthesizing the particulate polymer, various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the composition of the monomer composition used in polymerization was changed as necessary so that the type and molar fraction of various monomer units, particle size, and swelling degree in electrolyte in the obtained particulate polymer are as shown in Table 1. The results are shown in Table 1. In Table 1, the particulate polymers prepared in these examples, which differ from Example 1 in composition, etc., are indicated as particulate polymers BG, H, and J, respectively. In Table 1, the columns showing the type and molar fraction of the hydroxyl group-containing monomer unit in Example 7 and Example 10 are indicated as "NMA / β-HEA" and "0.03 / 0.05", respectively. The notation "NMA / β-HEA" indicating the type means that the particulate polymer contained two types of units, N-methylolacrylamide units and β-hydroxyethyl acrylate units, and the notation "0.03 / 0.05" indicating the molar fraction means that the molar fraction of the N-methylolacrylamide units was 0.03 and the molar fraction of the β-hydroxyethyl acrylate units was 0.05.

[0082] Example 8 In the <Preparation of slurry composition for heat-resistant layer> step, the non-conductive particles used were changed from alumina particles to barium sulfate particles (TS-2, manufactured by Takehara Chemical Industry Co., Ltd., volume average particle size D50 (catalog value): 0.3 μm), and the same operations, measurements, and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0083] Example 10 In synthesizing particulate polymer I, polymerization conditions were changed from the conditions in preparing particulate polymer G in Example 7 (specifically, the amount of emulsifier charged in reactor was changed to 0.02 parts). Except for this, various operations, measurements, and evaluations were carried out in the same manner as in Example 7. The results are shown in Table 1.

[0084] Example 12 In the <Preparation of slurry composition for heat-resistant layer> step, alumina particles having a larger diameter (AKP-3000, manufactured by Sumitomo Chemical Co., Ltd., volume average particle diameter D50 (catalog value): 0.7 μm) were used as the non-conductive particles, and the various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0085] Comparative Example 1 Parameter M of the resulting particulate polymer OH Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the composition of the monomer composition, etc., in synthesizing the particulate polymer was changed as necessary so that the value of / S was less than 0.4. The results are shown in Table 1. In Table 1, the particulate polymer prepared in this comparative example is represented as particulate polymer K.

[0086] Comparative Example 2 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the composition of the monomer composition in synthesizing the particulate polymer was changed as necessary so that the obtained particulate polymer would not contain a cyano group-containing monomer unit. The results are shown in Table 1. In Table 1, the particulate polymer prepared in this comparative example is referred to as particulate polymer L.

[0087] Comparative Example 3 The resulting particulate polymer does not contain a hydroxyl group-containing monomer unit, and naturally, the parameter M OH Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the composition of the monomer composition, etc., in synthesizing the particulate polymer was changed as necessary so that the value of / S was 0. The results are shown in Table 1. In Table 1, the particulate polymer prepared in this comparative example is represented as particulate polymer M.

[0088] Comparative Example 4 <Preparation of aqueous dispersion containing particulate polymer N> Into a reactor equipped with a stirrer, 70 parts of ion-exchanged water, 0.15 parts of sodium lauryl sulfate ("EMAL 2F" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.5 parts of ammonium persulfate were fed, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. On the other hand, in another vessel, 50 parts of ion-exchanged water, 0.5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 1.2 parts of N-methylolacrylamide as a hydroxyl group-containing monomer, 2 parts of acrylonitrile as a cyano group-containing monomer, and 93.8 parts of n-butyl acrylate, 2 parts of methacrylic acid, and 1 part of allyl glycidyl ether as other monomers were added, and 0.15 parts of a chelating agent (Chilest Co., Ltd.'s "Chilest 400G" (sodium ethylenediamine tetraacetate tetrahydrate)) were mixed to obtain a monomer composition. This monomer composition was continuously added to the reactor over 4 hours to perform polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the mixture was stirred for another 3 hours at 70°C, and then the reaction was terminated to produce an aqueous dispersion containing particulate polymer N (binder composition for heat-resistant layer). <Preparation of slurry composition for heat-resistant layer>~<Preparation of secondary battery> Except for using the binder composition for heat-resistant layer obtained as described above, the same operations, measurements, and evaluations were carried out in each subsequent step as in Example 1. The results are shown in Table 1.

[0089] In addition, in Table 1 shown below, "AN" indicates an acrylonitrile unit, "NMA" indicates an N-methylolacrylamide unit; "BA" indicates n-butyl acrylate units; "MAA" indicates a methacrylic acid unit, "Aam" indicates an acrylamide unit; "CMC" stands for carboxymethyl cellulose; "β-HEA" indicates β-hydroxyethyl acrylate units; "AMA" indicates an allyl methacrylate unit; "HEMA" indicates a hydroxyethyl methacrylate unit; "MAN" represents a methacrylonitrile unit; "2EHA" indicates 2-ethylhexyl acrylate units, "St" indicates a styrene unit, "AGE" indicates an allyl glycidyl ether unit, "Al2O3" indicates alumina particles, "BaSO4" refers to barium sulfate particles.

[0090] [Table 1]

[0091] From Table 1, it can be seen that the monomer contains a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, and further has a predetermined parameter M OH It can be seen that in Examples 1 to 12 using a binder composition containing a particulate polymer with a value of / S of 0.40 or more, a heat-resistant layer having a sufficiently high peel strength and exhibiting high adhesion to the substrate was obtained. It can also be seen that the heat-resistant layers of Examples 1 to 12 were capable of providing excellent cycle characteristics to the secondary battery. On the other hand, the copolymer does not have at least one of a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, and / or does not have a predetermined parameter M OHIn Comparative Examples 1 to 4, in which a binder composition containing a particulate polymer having a / S value of less than 0.40 was used, a heat-resistant layer with a sufficiently high peel strength could not be formed, and it was found that the adhesion of such a heat-resistant layer to the substrate was insufficient. [Industrial Applicability]

[0092] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery heat-resistant layer, which can prepare a slurry composition for a non-aqueous secondary battery heat-resistant layer capable of forming a non-aqueous secondary battery heat-resistant layer having sufficiently high peel strength. Moreover, according to the present invention, it is possible to provide a slurry composition for a heat-resistant layer for a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery having a sufficiently high peel strength. According to the present invention, it is possible to provide a heat-resistant layer for a nonaqueous secondary battery having a sufficiently high peel strength, and a nonaqueous secondary battery including the heat-resistant layer.

Claims

1. A binder composition for a heat-resistant layer of a non-aqueous secondary battery, comprising a particulate polymer, The particulate polymer comprises a cyano group-containing monomer unit and a hydroxyl group-containing monomer unit, The molar fraction M of the hydroxyl group-containing monomer unit in the particulate polymer OH is the surface area value S (μm 2 ) divided by (M OH / S) is 0.40 or more, the molar fraction of the cyano group-containing monomer unit in the particulate polymer is 0.07 or less; A binder composition for a heat-resistant layer of a non-aqueous secondary battery.

2. The volume average particle diameter of the particulate polymer is 0.30 μm or less, and 2. The binder composition for a heat-resistant layer of a nonaqueous secondary battery according to claim 1, wherein a molar fraction of the hydroxyl group-containing monomer unit in the particulate polymer is 0.02 or more.

3. The binder composition for a heat-resistant layer of a nonaqueous secondary battery according to claim 1 or 2, wherein the particulate polymer has a degree of swelling of 8.0 times or less in an electrolyte solution.

4. A slurry composition for a non-aqueous secondary battery heat-resistant layer, comprising: non-conductive particles; and the binder composition for a non-aqueous secondary battery heat-resistant layer according to any one of claims 1 to 3.

5. The slurry composition for a non-aqueous secondary battery heat-resistant layer according to claim 4 , wherein the non-conductive particles have a volume average particle size of 0.7 μm or less.

6. A heat-resistant layer for a non-aqueous secondary battery, formed using the slurry composition for a heat-resistant layer for a non-aqueous secondary battery according to claim 4 or 5.

7. A non-aqueous secondary battery comprising the heat-resistant layer for a non-aqueous secondary battery according to claim 6 .

Citation Information

Patent Citations

  • Separator for lithium battery, lithium battery including the same, and method of manufacturing lithium battery

    JP2015099777A

  • Composition for nonaqueous secondary battery functional layer, nonaqueous secondary battery functional layer, and nonaqueous secondary battery

    JP2016122611A

  • Composite separator for secondary battery and lithium secondary battery including the same

    JP2019102453A

  • Slurry for lithium ion secondary battery porous film, production method therefor, separator for lithium ion secondary battery, and lithium ion secondary battery

    WO2014148577A1